Urgency of Legal Pluralism Study for Students of Sharia and Law Faculty After Changes of Academic Degree - Sopyan, Yayan (Fakultas Syariah, 2020)
Abstract: Changes in Academic Degrees through Regulation of the Minister of Religion No. 33 of 2016 from Bachelor of Islamic Law to Bachelor of Law must be taken seriously by making concrete efforts to improve the quality of graduates. This regulation responds to the demands of a competitive job market. The consequence is that graduates of the Faculty of Sharia and Law have just not academic skills in the fields of Sharia and law at the same time but also have legal proficiency in the form of sensitivity to the value of justice that lives in society. Globalization accelerates social interaction. Indonesia is inevitably a plural country in which various legal systems are practiced, from customary law, religious law, national law, and international law. This study aims to analyze the reasons for the importance of legal pluralism studies taught to students of the Faculty of Sharia and law. This type of research is explanative and exploratory research. The results of this study indicate that the study of legal pluralism in the Faculty of Sharia and Law is still minimal and only inserted in certain sub-subjects. Even though the existence of this legal pluralism course is very urgent so that students have a sensitivity to the sense of justice that is the essence of law graduates, the implementation of it, legal pluralism must be an independent course or inserted into several relevant subjects.Keywords: Legal-Pluralism; Change of Bachelor's Degree; improving the quality of graduatesAbstrak: Perubahan Gelar Akademik melalui Peraturan Menteri Agama No 33 tahun 2016 dari Sarjana Hukum Islam menjadi Sarjana Hukum harus ditangapi dengan serius dengan melakukan upaya kongkret untuk meningkatkan mutu lulusan. Peraturan ini merespon dari tuntutan pasar kerja yang kompetitif. Konsekuensinya adalah lulusan Fakultas Syariah dan Hukum bukan saja memiliki kemampuan akademik dibidang ilmu Syariah dan ilmu hukum sekaligus, tetapi juga memiliki kemahiran hukum berupa kepekaan terhadap nilai keadilan yang hidup di masyarakat. Globalisasi mempercepat terjadinya interaksi sosial.Â Tidak dapat dielakkan bahwa Indonesia merupakan negara plural yang didalamnya dipraktikkan berbagai system hukum mulai dari hukum adat, hukum agama, hukum nasional, dan hukum internasional. Penelitian ini bertujuan untuk menganalisis alasan-alasan pentingnya kajian pluralism hukum diajarkan kepada mahasiswa Fakultas Syariah dan hukum. Jenis penelitian ini merupakan penelitian eksplanatif dan juga eksploratif. Hasil penelitian ini menunjukkan bahwa kajian pluralism hukum di Fakultas Syariah dan Hukum masih minim dan hanya disisipkan dalam sub-matakuliah tertentu. Padahal keberadaan matakuliah legal pluralism ini sangat urgen agar mahasiswa memiliki kepekaan terhadap rasa keadilan yang menjadi esensi dari sarjana hukum. Dalam implementasinya, pluralism hukum harus menjadi matakuliah yang mandiri, atau disisipkan pada beberapa matakuliah yang relevan.Â Kata Kunci: Pluralisme Hukum, Perubahan Gelar Sarjana, peningkatan mutu lulusan.